Porcelain aorta in a cat with feline leukemia virus and suspected mediastinal lymphoma (Research, Society and Development, 2024)
A five-year-old domestic cat with pleural effusion and renal failure was referred for cardiology evaluation. The cat had positive serology for feline leukemia virus (FELV) and was suspected of having mediastinal lymphoma. According to laboratory results, the patient's renal failure was classified as Chronic Kidney Disease (CKD) IRIS stage-3. Radiographic examination of the chest indicated a massive pleural effusion. After thoracocentesis, new chest radiographs revealed vascular calcification, extending from the aortic root to the abdominal aorta, including the celiac and cranial mesenteric arteries. It also demonstrated an increase in volume and calcification of both kidneys. Ultrasonography of the mediastinum showed a heterogeneous hypoechoic mass suggestive of lymphoma. The walls of the thoracic aorta were thickened and hyperechoic, concomitant with mild valve insufficiency. Due to the similarity of the patient's radiographic and echocardiograph findings with those described in humans with the so-called “porcelain aorta”, we propose the same nomination for this specific case. Extensive calcification of the aorta seems to be extremely rare in domestic cats, considering that the veterinary literature includes very few publications. The objective of this case report was to present the results of clinical history, laboratory, and image changes in a cat FELV-positive, suspected lymphoma, CKD, hypercalcemia, and evidence of extensive aorta calcification, concomitant to aortic valve insufficiency.